Hepatitis C seroconversion in methadone maintenance treatment programs in Wuhan, China. - Zhou, Wang; Wang, Xia; Zhou, Sheng; Xie, Nianhua; Liu, Pulin; Luo, Li; Peng, Jinsong; Liu, Manqing; Desrosiers, Alethea; Schottenfeld, Richard; Chawarski, Marek C (Addiction (Abingdon, England), 2014)
To decrease infectious disease transmission, China is expanding methadone maintenance treatment (MMT). This study evaluated the prevalence of hepatitis C virus (HCV) infection at MMT entry, seroconversion rates after admission, and potential risk factors for HCV seroconversion during MMT in Wuhan, China.